THE WOODEN TRACKWAY PR6, ASCHENER BOG, LOWER-SAXONY, GERMANY - A. Colson; M. Heumüller; E. Abbentheren (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
In northern Europe, wetlands hold valuable cultural heritage and enable the conservation of organic material. The region of Lower-Saxony (Germany) boarders the Netherlands in the West and the North Sea in the North. Until the era of cultivation and drainage large parts of northern Lower-Saxony were covered by bogs. Human populations have been living in this environment and developed strategies for crossings since the Neolithic period. There are about 500 wooden trackways listed in Lower-Saxony and several of them have been excavated. The wooden trackway PR6 located in the Aschener Bog, district of Diepholz has been excavated from 2019 to 2021 in cooperation with the natural park Dümmer and the Lower-Saxony State Service for Cultural Heritage (NLD). The project aimed to study a segment of about 550m, which was endangered by peat mining. The company DENKMAL3D (D3D) was contracted for the project and conducted the excavation on site supervised by Dr. M. Heumüller (NLD). Additionally, several staff members from D3D were involved in different capacity: 3D documentation, surveying, and conservation-restoration. This contribution shows the importance of interdisciplinarity in an archaeological research project involving organic material, which is very challenging to excavated and to conserve long-term. Which ethical decision had to be made and how did 3D documentation played a central role in supporting this process? The technical details will be presented as well as future perspective will be discussed and the following research project shortly mentioned.